An integrative overview of physiological and proteomic changes of cytokinin‐induced potato (Solanum tuberosum L.) tuber development in vitro. Issue 3 (12th August 2019) - Cheng, Lixiang; Wang, Dongxia; Wang, Yuping; Xue, Hongwei; Zhang, Feng
Abstract : Potato tuberization is a complicated biological process regulated by multiple phytohormones, in particular cytokinins (CKs). The information available on the molecular mechanisms regulating tuber development by CKs remains largely unclear. Physiological results initially indicated that low 6‐benzylaminopurine (BAP) concentration (3 mg l −1 ) advanced the tuberization beginning time and promoted tuber formation. A comparative proteomics approach was applied to investigate the proteome change of tuber development by two‐dimensional gel electrophoresis in vitro, subjected to exogenous BAP treatments (0, 3, 6 and 13 mg l −1 ). Quantitative image analysis showed a total of 83 protein spots with significantly altered abundance (>2.5‐fold, P < 0.05), and 55 differentially abundant proteins were identified by MALDI‐TOF/TOF MS. Among these proteins, 22 proteins exhibited up‐regulation with the increase of exogenous BAP concentration, and 31 proteins were upregulated at 3 mg l −1 BAP whereas being downregulated at higher BAP concentrations. These proteins were involved in metabolism and bioenergy, storage, redox homeostasis, cell defense and rescue, transcription and translation, chaperones, signaling and transport. The favorable effects of low BAP concentrations on tuber development were found in various cellular processes, mainly including the stimulation of starch and storage protein accumulation, the enhancement of the glycolysis pathway and ATP synthesis, the cellular homeostasis maintenance, the activation of pathogen defense, the higher efficiency of transcription and translation, as well as the enhanced metabolite transport. However, higher BAP concentration, especially 13 mg l −1, showed disadvantageous effects. The proposed hypothetical model would explain the interaction of these proteins associated with CK‐induced tuber development in vitro.